Analisis Frekuensi Perdagangan, Volume Perdagangan dan Kapitalisasi Pasar Terhadap Return Saham Pada Perusahaan Perbankan BUMN Terdaftar di Bursa Efek Indonesia - Suwandi Suwandi; Muhammad Ali Lutfi; Prasetya Tri Mahendra; Irawati Yunifah (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2023)
This study aims to determine whether there is an influence on the return of banking stocks in the BUMN sector, which is seen based on trading frequency, trading volume and market capitalization. This type of quantitative research uses the event study method. The population and sample used are all BUMN banks listed on the Indonesia Stock Exchange. This hypothesis testing is a different test using the Wilcoxon Test, namely the Z test, through SPSS. The results showed that there was no significant influence between the frequency and volume of trading with stock returns, but market capitalization had a significant influence on stock returns. While simultaneously on the overall influence of independent variables on stock returns in BUMN banking companies.